Analisis Faktor-faktor yang Memengaruhi Keputusan Pembelian Makanan Khas Daerah Secara Online oleh Konsumen Wanita di Indonesia - Fauziah, Irma; Rahmaningtyas, Avivah; Cahyaningtyas, Nur Indah; Novitaningrum, Restie; Putri, Levana Masitajasmin; Fadhilah, Muhammad Luthfie; Simamora, Liska (Universitas Galuh, 2026)
The rapid growth of e-commerce has transformed consumer behavior, particularly in the process of making online purchase decisions. This study aims to analyze the influence of price perception, trust, ease of use, and perceived risk on online purchase decisions among female consumers. The focus on female consumers is essential, given their high participation in online shopping activities and distinct psychological characteristics compared to men, such as heightened sensitivity to price and risk. The sampling technique used in this study was non-probability sampling with a purposive sampling approach, involving 105 respondents. The analytical method employed was quantitative using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that all four independent variables—price perception, trust, ease of use, and perceived risk—have a significant influence on online purchase decisions. Price perception emerges as the most dominant factor, indicating that female consumers are highly responsive to discounts and promotional strategies. Trust also plays a crucial role, especially for those who have no prior experience shopping on the platform. Perceived risk has a negative influence, reflecting concerns about transaction security and uncertainty regarding product quality. Meanwhile, ease of use contributes positively to purchase decisions through smooth navigation and system efficiency.